Patient with Herlyn–Werner–Wunderlich syndrome and endometriosis achieves successful full-term pregnancy (40 weeks and 6 days): a case report - Juliana Vieira Queiroz Almeida Oliveira; Chris Elizabeth Philip; Thayná Andreza Ribeiro Pereira; Gabriela Martins Perez Garcia; Quésia Tamara Mirante Ferreira Villamil (Journal of Medical Case Reports, 2024)
Abstract Introduction Herlyn–Werner–Wunderlich syndrome , a rare Müllerian ducts congenital disease, is characterized by a diphtheritic uterus, blind hemivagina, and ipsilateral renal agenesis. Diagnosis is at young age by ultrasound and magnetic resonance imaging, and the prognosis is good. Usually, complications evolve endometriosis and secondary pelvic inflammation. Case report A 40-year-old female patient, Brazilian, white, primigravida, diagnosed at 30 years with a didelphic uterus on ultrasound, and 4 years later, with a left ovarian endometrioma, multiple ovarian cysts, and left renal agenesis on magnetic resonance imaging. Subsequently, due to dyspareunia and a feeling of swelling, the patient underwent transvaginal ultrasound with bowel preparation, and a hematocolpos was found and Herlyn–Werner–Wunderlich syndrome was suspected; 10 years after the diagnosis she had a planned pregnancy. She presented frequent contractions following the 15th week of pregnancy and fortunately there were no complications or premature labor. Labor was inducted at 40 weeks and 6 days without progress and a cesarean section was indicated and performed without complications. Herlyn–Werner–Wunderlich syndrome often goes unnoticed, leading to inadequate treatment. Individuals with Herlyn–Werner–Wunderlich syndrome commonly face fertility issues, such as high miscarriage rate (21–33%), and obstetric complications, such as spontaneous abortions (40% risk), intrauterine growth restriction, postpartum hemorrhage, increased fetal mortality, preterm delivery (21–29%), and elevated rates of cesarean sections. In addition, there is higher susceptibility of developing endometriosis, especially with hemivaginal obstruction, and pelvic adhesions. Conclusion Early diagnosis enables timely treatment and, consequently, fewer complications. Still, when these factors are absent, vaginal birth may still be possible. The true prevalence and incidence of complications related to Herlyn–Werner–Wunderlich syndrome are still unknown.